Factors Influencing Military Nurses' Reporting of Patient Safety Events in South Korea: A Structural Equation Modeling Approach - Sookhee Yoon; Taewha Lee (Elsevier, 2022)
Summary: Purpose: This study explored how just culture, authentic leadership, safety climate, patient safety knowledge, and safety motivation all affect military nurses' reporting of patient safety events. Methods: This study adopted a cross-sectional and descriptive correlational design. Data were collected from 303 nurses working across eight military hospitals under the jurisdiction of the Armed Forces Medical Command in South Korea, from June 17 to July 25, 2020. The hypothesized model was then validated using structural equation modeling. Results: The participating military nurses did not show any proactive attitudes toward reporting near misses when compared with their responses to adverse or no-harm events. The final model exhibited goodness of fit. Herein, both safety climate (β = 0.35, p = .009) and patient safety knowledge (β = 0.17, p = .025) directly influence patient safety event reporting. Moreover, just culture indirectly influences patient safety event reporting (β = 0.31, p = .002). The discovered influencing factors account for 22.9% of the variance in explaining patient safety event reporting. Conclusions: Our findings indicate that just culture, safety climate, and patient safety knowledge either directly or indirectly affected patient safety event reporting among military nurses. These findings then serve to provide a theoretical basis for developing more effective strategies that would then improve military nurses' patient safety behaviors.